Design of Microchannel Heat Exchanger in Air Conditioner System with Propane as Working Fluid - Endrayana Sudarno, Galih
The Kigali Amendment to the Montreal Protocol requires each country to reduce HFC production and consumption. The most widely used HFC in residential conditioning machines is R134a. R134a in the use of air conditioning machines can be replaced with propane. However, in the use of propane, the nature of its burning needs to be considered. One of the solutions to this problem is the reduction of the refrigerant load by reducing the volume of the heat exchanger. The purpose of this study is to design a microchannel heat exchanger on an air conditioning machine with propane as working fluid. The design of the heat exchanger is done by the Number of Transfer Unit method. The design of the heat exchanger uses the Genetic Algorithm to obtain the optimum heat exchanger dimensions. Variables to be optimized are diameter, number of channels per tube and number of tubes. The objectivity function used in genetic algorithms is minimal volume. The working temperature of the evaporator and condenser are 299 and 328 K. The heat transfer rates on the evaporator and condenser are 2210 and 3215 W with a propane mass rate of 0.0079 kg/s. Based on the design results, the main dimensions of the evaporator are 12 ?m diamater, the number of canals per tube 90 and the number of tubes 12. In the condenser, the main dimension values are 111 ?m diameter, the number of channels per tube 193 and the number of tubes 20. Fins used in the heat exchanger is a louver fin with the D12 series. Changes in subcooling and superheat temperature on evaporator and condensor inflict changes in the length with value 1.4% and % from it’s initial length. Effect of change of air temperature to 308 K on condensor is 5.2% addition of it’s intial length for condensor.